Identification of the electrical connection in the catalyst layer of the polymer electrolyte membrane water electrolyzer. (8th April 2022) - Kwen, Jiyun; Doo, Gisu; Choi, Sungyu; Guim, Hwanuk; Yuk, Seongmin; Lee, Dong-Hyun; Lee, Dong Wook; Hyun, Jonghyun; Kim, Hee-Tak
Abstract: Mechanical deterioration of the catalyst layer (CL) in contact with the porous transport layer (PTL) can disconnect it from the electrical network and deactivate it during proton exchange membrane water electrolysis (PEMWE). This study presents a method for visual identification of the electrically connected region in the CL using in situ electrochemical reduction of iridium oxide to iridium, coupled with energy dispersive X-ray spectroscopy (EDS) mapping and environmental scanning electron microscopy (E-SEM) analyses. Because the iridium oxides in the catalyst layer can be electrochemically reduced to iridium only when they are in both ionic and electronic connection, the reduced portion corresponds to electrically connected region. Our results revealed that the region under the rib not in contact with porous transport layer (PTL) (non-PTL-contact region) is the most prone to electric disconnection because of the cracks formed by PTL compression. Finer CL fragmentation at lower catalyst loadings aggravates such disconnection. Cell polarization of a low catalyst-loaded CL is greatly reduced when the electrical connection at the non-PTL-contact region under the rib is improved with the addition of carbon nano-fibers to the CL. These results emphasize the importance of the electrical connection in the non-PTL-contact region for achieving high-performance low-catalyst-loaded PEMWE. Highlights: The utilization of the catalyst layer in polymer electrolyte water electrolysis is studied. Electrically-connected region is identified using electrochemical reduction of iridium oxide. The portion of catalyst layer not in contact with porous transport layer under rib is less utilized. Cracking behavior is responsible for the electric-disconnection of the catalyst layer.